The status of the academic library profession in Isabela an assessment - Enriquez, Zoilo Canceran (2005)
Academic librarians of today have a significant role and are considered special agents of colleges and universities in contributing towards the realization of the institutional mission and vision. The librarians are actively involved in the formulation and implementation of the colleges' and universities' goals and objectives. Thus, the academic library profession in Isabela deserves recognition from the public.